Pengaruh Pembelajaran Online pada Masa Pandemi Covid-19 terhadap Hasil Belajar Mata Pelajaran Ilmu Pengetahuan Sosial Siswa Kelas VIII di SMP Walisongo Bekasi - Subur, Jang Mas; Rista, Nadia (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
Basically learning outcomes are the interaction of teaching and learning activities that produce new attitudes and skills from a lesson. The purpose of this study was to find out how well online learning during the Covid-19 pandemic period affected student learning outcomes in social science subjects. This research is included in the comparative quantitative notion, the researcher wants to know whether there is an influence on the determined variables. The research source was the eighth grade students of SMP Walisongo Bekasi, amounting to 35 students. The results showed that the effect of online learning during the Covid-19 emergency on student learning outcomes in social science subjects affected student learning outcomes. This is evidenced by the acquisition of sig = 0.004> 0.05 and Fcount = 2.491.